2021
DOI: 10.1002/jsfa.11259
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of biofortified crops: consumer acceptance of pasta from yellow cassava and leafy vegetables

Abstract: BACKGROUND: Newly developed yellow biofortified cassava has been adjudged as a cost-effective solution to vitamin A deficiency in low-and middle-income countries with high cassava intake such as Nigeria. In this study, yellow cassava was developed into a novel pasta enriched with amaranth vegetable and tested among consumers. Attitudes, perception, motives for consumption and perceived barriers were ascertained using focus group discussions and randomised face-to-face interviews, while liking, preference and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The carotenoid contents of BRS 399 and BRS 396 (biofortified) were similar to that of the cultivar "Gema de ovo", with no significant difference between the analyzed samples of cultivars with yellow pulp. The possibility of adding nutritional qualities to the cassava roots (biofortification) directed the breeding programs towards the selection of table cassava clones with yellow root coloring since there is a positive correlation between the intensity of the yellow coloring of the roots and their carotenoid levels (Chávez et al, 2005;Lawal et al, 2021), which was found in this study. In addition, biofortified cultivars have high productive potential, have a structure that facilitates crop treatment and harvesting, are more resistant to the main pests and diseases, in addition to having high agronomic and technological value (Silva et al, 2014).…”
Section: Cultivarssupporting
confidence: 52%
“…The carotenoid contents of BRS 399 and BRS 396 (biofortified) were similar to that of the cultivar "Gema de ovo", with no significant difference between the analyzed samples of cultivars with yellow pulp. The possibility of adding nutritional qualities to the cassava roots (biofortification) directed the breeding programs towards the selection of table cassava clones with yellow root coloring since there is a positive correlation between the intensity of the yellow coloring of the roots and their carotenoid levels (Chávez et al, 2005;Lawal et al, 2021), which was found in this study. In addition, biofortified cultivars have high productive potential, have a structure that facilitates crop treatment and harvesting, are more resistant to the main pests and diseases, in addition to having high agronomic and technological value (Silva et al, 2014).…”
Section: Cultivarssupporting
confidence: 52%
“…The particle size influences starch behaviour; while lower onset gelatinisation temperatures, peak, final and hold viscosities with a decrease in particle sizes have also been reported (Chisenga et al, 2019;Ahmed et al, 2018). However, in a separate study, the protein content of the yellow cassava flours was found lower than wheat flour at 0.99-2.95 g/100 g while the total dietary fibre was comparable at between 9.0 and 10.0 g/100 g dry weight (Lawal, Talsma, Bakker, Fogliano, & Linnemann, 2021).…”
Section: Particle Size Distribution (Psd) Of Flour Samplesmentioning
confidence: 73%
“…Fluted pumpkin (Telfairia occidentalis), known as "ugwu" in Nigeria, is the most preferred, widely cultivated leafy vegetable in Nigeria (Lawal, Talsma, Bakker, Fogliano, & Linnemann, 2021). The leaves are good sources of vitamins (Vit.…”
Section: Introductionmentioning
confidence: 99%
“…While a large number of existing studies have investigated the health impacts of and consumer attitude toward biofortified food (Birol et al., 2015; De Groote et al, 2011; De Steur et al, 2010, 2015; Huang et al., 2021; Lawal et al., 2021; Stein et al., 2005), much less effort is on understanding producer valuation on biofortified crop planting in developing countries. One may assess producer valuation of a biofortified crop variety through their willingness to pay (WTP) for biofortified crop seeds (Maredia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%